PENERAPAN DISPENSASI PERKAWINAN ANAK DI BAWAH UMUR MENURUT HUKUM POSITIF DI INDONESIA (STUDI ANALISIS PENETAPAN PENGADILAN AGAMA BENGKULU NOMOR 0051/PDT.P/2016/PA.BN) - Iskandar, Humam (UIN Fatmawati Sukarno Bengkulu, 2017)
Humans need to carry out marriage in order to legalize the relationship between the prospective husband or wife. Given the importance of marriage to human life, it is appropriate for marriage rules to be regulated in such a way that it can minimize the occurrence of problems in the field of marriage. One important thing to realize orderly in the field of marriage is the existence of legal certainty in the field of marriage, especially on marriage dispensation in prospective husband / future wife whose age has not been eligible by law. The law governing marriage is Law no. 1 of 1974 and the Compilation of Islamic Law. One of the issues discussed in the Act and KHI is the minimum age limit for marriage. Therefore it must be prevented the existence of underage marriage. The type of research used is qualitative research, which produces descriptive data in the form of words or oral from people and observed behavior. Based on the formulation of problems and research objectives, the approach method used is the sociological juridical approach. Means that this study could include research on legal principles, legal systematics, legal synchronization, legal history, and comparative law. While the sociological means this research consists of research on legal identification (not written) and research on the effectiveness of the law. Research location in Religious Court of Bengkulu City. The data used in this study consist of primary data and secondary data. Data obtained from both the literature and the interview will be analyzed by using qualitative analysis method, a research procedure that produces analytical descriptive data. In this analysis, the authors conclude that the determination of the dispensation has been juridically appropriate. While the sociological reasons proposed by the applicant is not in an ideal position. This lack of ideals is due to the fact that the applicant does not have a plan to mature marriage, the status of the applicant who is still a student, and has not / does not have a job or income to support the family.